3x+13=-3x+73

Simple and best practice solution for 3x+13=-3x+73 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+13=-3x+73 equation:


Simplifying
3x + 13 = -3x + 73

Reorder the terms:
13 + 3x = -3x + 73

Reorder the terms:
13 + 3x = 73 + -3x

Solving
13 + 3x = 73 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
13 + 3x + 3x = 73 + -3x + 3x

Combine like terms: 3x + 3x = 6x
13 + 6x = 73 + -3x + 3x

Combine like terms: -3x + 3x = 0
13 + 6x = 73 + 0
13 + 6x = 73

Add '-13' to each side of the equation.
13 + -13 + 6x = 73 + -13

Combine like terms: 13 + -13 = 0
0 + 6x = 73 + -13
6x = 73 + -13

Combine like terms: 73 + -13 = 60
6x = 60

Divide each side by '6'.
x = 10

Simplifying
x = 10

See similar equations:

| (2v+14)(v^2-8v+12)=0 | | 14t+15=10t+31 | | 8x-1=642x | | 2t-7=t+2 | | z^2+(4+i)*z-6+6i=0 | | 6h+20=720 | | 2b-50+b+2b-2+30+b-25+44+b-22=360 | | 2n-15=45 | | -3(4+2)=4-22 | | 4n+12=7n+9 | | 3w-23+3w-33+4w+4w-46+49+3w-39+61=360 | | 2x*2x-9x+2=0 | | 2x+2(3x+1)+3x-1=7x+1 | | 6x+6=6x-5 | | 2x+45=x-32 | | 60.5+90+x=180 | | 3w-23+3w-33+4w-46+3w-39+49+61=360 | | 6(x+1)-(p+1)=6x+3 | | 7k^3+2x=0 | | 12s=16+6s+19 | | 7y-9=-2 | | x*x-4.5x+0.5=0 | | x(5x-6)=0 | | x^2-2=7-y^2 | | 6x+7=5x+-11 | | 5(-3+2)-9=-17+3 | | 13/24×-5x | | 10x^2+35=0 | | 63/1-54/9 | | X^2+y^2-12x+8y+7=0 | | 5(-3+2)-9=-17-3 | | 5x+3y-4=4 |

Equations solver categories